(untitled) (Itinera, 2024)
The article intends to explore the hypothesis that there is not only a reproductive dimension to memory but also concerns the terrain of poiesis. Between memory and creativity, there seems to be a point at which the crossing of the perception in the immanent time changes direction and becomes a creative attitude. In this regard, we investigate a particularly significant period in the history of Western thought, and in the constitution of modernity, namely the passage from the Middle Ages to the Renaissance. In our path, we intend to emphasise, on the one hand, the permanence of the problem of a memory that opens up to poiesis; on the other, how in this epochal passage significant variations are made in the way of understanding poietic memory and in the way in which the criterion that organises pre-existing data functions for the construction of the work. A path through the reflections of Augustine, Bonaventure, Leon Battista Alberti, and Leonardo da Vinci is proposed to address this theme.